The Effect of Gadget Addiction on Learning Interest among Grade XI Students at State Vocational High School 9 Padang - Widia Widia; Linda Fitria; Indra Wijaya (Universitas PGRI SUMATERA BARAT, 2026)
This study aims to examine the effect of gadget addiction on students’ learning interest among Grade XI students at SMKN 9 Padang in the odd semester of the 2025/2026 academic year. The study employed a quantitative correlational design. The population consisted of 444 Grade XI students, and 210 students were selected as the sample through proportional random sampling. Data were collected using two Likert-scale questionnaires measuring gadget addiction and students’ learning interest. The data were analyzed using descriptive statistics, normality testing, linearity testing, and simple linear regression with the assistance of Microsoft Excel and SPSS. The results showed that the gadget addiction variable had a mean score of 111.53, while the learning interest variable had a mean score of 122.90. The Kolmogorov-Smirnov normality test indicated that both variables were normally distributed, with significance values of 0.276 for gadget addiction and 0.929 for learning interest. The regression analysis showed that gadget addiction significantly predicted students’ learning interest, with B = 0.658, Beta = 0.639, t = 11.976, and p < 0.001. The regression equation was Y = 49.498 + 0.658X, indicating that every one-point increase in the gadget addiction score was associated with a 0.658-point increase in the learning interest score. The coefficient of determination was approximately 0.408, meaning that gadget addiction explained 40.8% of the variance in students’ learning interest. These findings indicate a significant positive relationship between gadget addiction scores and learning interest scores in the scoring system used in this study. However, this result should be interpreted cautiously because the finding differs from the dominant theoretical assumption that uncontrolled gadget use tends to reduce academic engagement. The result may indicate that the instrument captured broader gadget engagement, including learning-related use, rather than purely maladaptive addiction. Therefore, schools need to strengthen digital self-regulation, responsible gadget use, and guidance and counseling services to ensure that students’ use of gadgets supports learning rather than distracts from it.